Le nozze di Alisia di Châtillon con Azzo VI d’Este (1204). Alle origini dei rapporti fra Estensi e Ungheria al tempo di papa Innocenzo III - Pallotti, Riccardo (Verbum – Analecta Neolatina, 2022)
Firstly based on sources of the Modena State Archive, the essay focuses on the political and dynastic relations between the House of Este and the Kingdom of Hungary under king Imre Árpád (1196–1204) and pope Innocent III (1198–1216), providing a brief insight into relations between West and East (Papacy, Árpád House, Latin princedom of Antiochia and Byzantine empire) that served as background to the marriage between Alisia of Châtillon, Hungarian king’s aunt, and the margrave of Este. Focusing on the political context of this dynastic union, the essay aims at proving that the marriage between the daughter of Raynald of Châtillon and Azzo VI could be related to the crusader ideology of Innocent III and to his political relations as with king Imre in Hungary as with the Este margraves in northeast Italy. Letters of Innocent III confirm his political interest in Hungary and his support to Imre in the civil war against Andrea.